Numerical Simulation on Conventional Ventilation System for Hospital Operating Room - Saif, Eiad; Al-Nehari, Hamoud A.; Asaad, Abdul Raqib Abdo (University of Science and Technology, Yemen, 2016)
Communities in the poor countries suffer from poor quality of health services. In the Republic of Yemen as one of those countries, some hospitals especially medium and small suffer of many problems which adversely affect health community life. This paper presents a case study conducted in a hospital operating room in Yemen, also computational fluids dynamics (CFD) analysis of the airflow, and temperature distribution are presented and discussed. The operating room model includes a patient lying on an operating table, four surgical staff, two air supply and four air exhausts. Results of simulation show a good agreement with experimental data from the literature and adopted standard. It is found that the airflow and air velocity significantly affects the thermal comfort of all workers in the operating room. Therefore, the air that enters the operating room is very importance and affects the room temperature. It is observed that the application of CFD in hospitals will give rise to design the internal environment and improved health outcomes especially in a country like Yemen.